Shale shakers and drilling fluid systems : techniques and technology for improving solids control management. (Gulf Pub. Co., 1999)
This comprehensive guide describes the various aspects of shale shaker design, applications, and improvements for maximizing efficiency. Drilling engineers will find technical data for better understanding and design of shale shakers; and foremen and derrickmen will discover valuable, practical insights to achieve optimum shaker performance. The guide helps prevent problems of solid controls by clearly describing design, application, and nomenclature of shale shakers, screens, and screen panels. In addition it explains many other aspects of complete solids control management. Written by experts for engineers and operations personnel Comprehensive guide describes the various aspects of shale shaker design Provides clear, concise information.